A representação da identidade nacional em figuras femininas de Aluísio Azevedo - Dresch, Graciela (2005)
This research has as objective to investigate on the representation of national identity in female characters of Aluísio Azevedo. Once the analyzed novels are classified as naturalists, it is necessary a study of the main features of Naturalism, movement developed in Brazil in the last decades of the nineteenth century. Moreover, by the fact that the referred period and the author had been influenced by the ideas of Comte, Darwin, Renan, Spencer, the selected approach to the study of the novels analyzes critically the Positivism. It is feasible to find out in the work of Aluísio Azevedo some elements considered by many scholars as the basis that form a nation, and that makes possible to discuss about the construction of national identity. Also, it can be noticed that in the novels O mulato, Casa de pensão and O cortiço, the female characters are very expressive. Therefore, with some emphasis in the aspects of national identity construction and gender, a critical reading of those novels can be made, mentioning aspects concerned with environment, race and moment.